2013
DOI: 10.1038/aps.2013.2
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of a novel curcumin analog P1 as potent inhibitor of the NF-κB signaling pathway with distinct mechanisms

Abstract: Aim: Curcumin has shown promising anticancer activity, which relies on its inhibition on NF-κB pathway. In this study, we characterized the pharmacological profile of a novel curcumin analog P1 and elucidate the related mechanisms. Methods: HEK293/NF-κB cells, stably transfected with an NF-κB-responsive luciferase reporter plasmid, were generated for highthroughput screen (HTS). Eight cancer cell lines, including PC3, COLO 205, HeLa cells etc. were tested. Cell viability was assessed using the sulforhodamine B… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 39 publications
(23 citation statements)
references
References 54 publications
0
23
0
Order By: Relevance
“…Stable HE K293/NF‐ κ B cells were seeded into 96‐well cell culture plates (Corning, NY, USA) and allowed to grow for 24 h. The cells were then treated with compound in 6 doses at a dilution ratio of 1:3, followed by stimulation with 10 ng mL −1 TNF‐ α . After 6 h, the luciferase substrate (Promega, Madison, WI, USA) was added to each well, and the released luciferin signal was detected using an EnVision microplate reader (Perkin–Elmer, Waltham, MA, USA).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Stable HE K293/NF‐ κ B cells were seeded into 96‐well cell culture plates (Corning, NY, USA) and allowed to grow for 24 h. The cells were then treated with compound in 6 doses at a dilution ratio of 1:3, followed by stimulation with 10 ng mL −1 TNF‐ α . After 6 h, the luciferase substrate (Promega, Madison, WI, USA) was added to each well, and the released luciferin signal was detected using an EnVision microplate reader (Perkin–Elmer, Waltham, MA, USA).…”
Section: Methodsmentioning
confidence: 99%
“…Stable HE K293/NF-kBc ells [18] were seeded into 96-well cell culture plates (Corning, NY,U SA) and allowed to grow for 24 h. The cells were then treated with compound in 6d oses at ad ilution ratio of 1:3, followed by stimulation with 10 ng mL À1 TNF-a.A fter 6h,t he luciferase substrate (Promega, Madison, WI, USA) was added to each well, and the released luciferin signal was detected using an EnVision microplate reader (Perkin-Elmer,W altham, MA, USA). IC 50 values were derived from an onlinear regression model (curvefit) based on as igmoidal dose response curve (variable slope) and computed using Graphpad Prism version 5.02 (Graphpad Software).…”
Section: Hek293/nf-k Kbluciferase Assaymentioning
confidence: 99%
“…It has been shown that the activation of NF-κB signaling in PCa cells correlates with PCa progression, chemoresistance, recurrence, and metastasis [82,83] . Thus, inhibiting NF-κB can suppress chemoresistance, and mediate antitumor responses while enhancing the sensitivity of tumor cells to other anticancer drugs [82] . Several studies have focused on targeting the NF-κB pathway on its own or in combination with conventional agents [84] .…”
Section: Nf-κb Pathwaymentioning
confidence: 99%
“…HEK293/NF-κB cells were prepared as reported [16]. The luciferase assay procedure was performed according to the reported methods [17].…”
Section: Luciferase Assaymentioning
confidence: 99%